1279 Does Multimorbidity Influence the Outcomes of Total Hip Replacement for Osteoarthritis?. (12th October 2021) - Ferguson, R; Prieto-Alhambra, D; Peat, G; Jordan, K; Valderas, J; Yu, D; Glyn-Jones, S; Silman, A
Abstract: Introduction: Limited data are available on the influence of multimorbidity on the outcomes of total hip replacement for patients with hip osteoarthritis, including the rate of complications and degree of functional benefit. The aim of this study was to investigate the influence of multimorbidity on the outcomes of total hip replacement in the UK. Method: A cohort study was performed, with cohort comprised of all patients over 65 years with a diagnosis of hip osteoarthritis recorded in Clinical Practice Research Datalink and receipt of primary total hip replacement recorded in Hospital Episode Statistics Admitted Patient Care. Severity of multimorbidity burden was measured using four different scores (Charlson Comorbidity Index, Electronic Frailty Index, count of drugs prescribed, count of primary care interactions). The outcomes were (i) the risks of total hip replacement, assessed by serious post-operative complications within 90 days (analysed with logistic regression), and (ii) the benefits of surgery, assessed by post-operative Oxford Hip Score (OHS) and EQ-5D quality of life score (analysed with linear regression). Results: 6, 682 patients were included. The rate of complications was 3.2%. Patients with severe multimorbidity burden were at 1.5 to 2.5 times increased risk of complications than patients without multimorbidity. There was no clinically meaningful difference in the benefits of surgery between patients with and without multimorbidity, irrespective of the method of scoring multimorbidity. Conclusions: Even for patients with severe multimorbidity burden, the potential benefits of total hip replacement for osteoarthritis remain substantial, while the increase in risk is relatively small.